P68 Changing demographics of the cystic fibrosis population with ageing – how will this impact future provision of care?. (11th November 2022) - Sapru, K; Bright-Thomas, R; Patterson, S; Barry, PJ; Jones, AM
Abstract : Introduction and Objectives: Survival in Cystic Fibrosis (CF) is increasing with advancing therapeutic options. CF patients aged ≥40 years represent a growing, heterogeneous group that constitute a large proportion of the total patient cohort at our centre. Our objectives were to characterise the demographics of the CF population aged ≥40 years and identify areas that will impact the provision of future CF care. Methods: Retrospective study of CF patients aged ≥40 years attending a large CF centre from August 2018–2021. Data collected included genotype, spirometry, body mass index (BMI), exocrine pancreatic status, predominant respiratory pathogen, CF-related diabetes (CFRD) and renal function. Results: The number of patients aged ≥40 years increased during the 4-year study period, from n=82 to n=92.Within this group the proportion of patients aged >50 years increased from 29% to 46%. Phe508del / Phe508del was the most common genotype and >80% of patients were pancreatic insufficient at all measured timepoints ( table 1 ). Median ppFEV1 improved from 49% [34–71%] to 62% [48–82%] (p<0.001) and the number of people with a FEV1 <30% reduced from 11 to 7 (7.6% of cohort in 2020). Median BMI did not change significantly moving from 23.6 [21.9–26.0] to 23.9 [22.5- 26.1] kg/m 2 . P. aeruginosa was the predominant organism isolated each year. The number of patients with mild renal impairment, with an estimated glomerular filtration rate (eGFR) between 60–89 mL/min/1.73 m 2, increased from 16% in 2018 to 27% in 2021. The number of CF patients aged ≥40 years with a diagnosis of CFRD also increased, n=39 in 2018 versus n=46 in 2021. The number of patients on modulator treatment increased from 27% (n=22) to 82% (n=72). Conclusion: A significant proportion of CF patients with severe CFTR genotypes and classical phenotypic CF, previously associated with poor prognosis, are surviving longer. The proportion of these older patients now taking CFTR modulators is high. They have improved lung function and fewer have severe lung function impairment. Increased longevity is accompanied by complexities of ageing including end organ damage such as renal impairment and CFRD. Further research is required to assess the full impact of newer CFTR modulators on the older population.